Teacher’s Perceptions of Electronic Multi Representation STEM based Worksheet to Improve Student’s Metacognitive Ability - Atika Putri; Dewi Lengkana*; Tri Jalmo (Universitas Syiah Kuala, 2022)
Science teachers often conduct a teacher-centered learning process without analyzing the essential needs of each student. Yet, it may not support student to enhance their cognition ability in 21th century era. This study aimed to describe teachers' perception toward usage of electronic multi representation-STEM based worksheet. The study was conducted in February 2021, involving 245 student and 15 science teachers of junior high school. The research used a mixed method with Sequential Explanatory Design. Data were taken using Questionnaire, interview, and to analyze current student worksheet. Data were analyzed descriptively. The data analysis techniques are data collection, data reduction, data display, and verification. The result shows that student have a positive perception toward usage of the electronic multi representation-STEM based worksheet. Almost all the teachers did not use the STEM approach to teach science. The current worksheets has not completely train students' metacognitive abilities and the students` metacognition was in low category, teacher has not use proper learning strategies, method, and visualize concepts in multi representation. It can be concluded that a STEM-based multi-representation worksheet is needed to improve students` metacognitive abilities of junior high school